Manajemen Pendidikan Islam MANAJEMEN SEKOLAH DALAM MEMBUDAYAKAN LITERASI MEDIA DAN PENERAPAN TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP BUKIT ASAM TANJUNG ENIM: SCHOOL MANAGEMENT IN CULTIVATING MEDIA LITERACY AND THE APPLICATION OF TECHNOLOGY IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT SMP BUKIT ASAM TANJUNG ENIM - Saipul Anwar; Ikas Kasenda; Edi Zalharis; Leny Marlina; Febriyanti, Febriyanti (Irfani, 2025)
Abstract Improving the quality of education is the main goal in the Indonesian education system, especially in Islamic religious education. One approach that can be applied is through effective school management in cultivating media literacy and the application of technology in Islamic Religious Education (PAI) learning. This study aims to examine the implementation of school management in cultivating media literacy and the application of technology in PAI learning at SMP Bukit Asam. The method used in this study is descriptive qualitative with data collection through interviews, observations, and documentation. The results of the study indicate that the use of technology in learning and the media literacy program through "Dear Time" has succeeded in improving the quality of students' understanding of PAI material, although there are still some obstacles in terms of technology access and students' understanding of the use of digital media. Optimal implementation of technology can enrich students' learning experiences and support improving the quality of education in schools. Keywords: Media Literacy, Technology, School Management, Education Quality.